Electronic transport property in Weyl semimetal with local Weyl cone tilt. (21st February 2018) - Jiang, Liwei; Feng, Lanting; Yao, Haibo; Zheng, Yisong
Abstract: In realistic materials of Weyl semimetal (WSM), the Weyl cone tilt (WCT) is allowed due to the absence of Lorentz invariance in condensed matter physics. In this context, we theoretically study the electronic transport property in WSM with the local WCT as the scattering mechanism. In so doing, we establish an electronic transport structure of WSM with the WCT occurring only in the central region sandwiched between two pieces of semi-infinite WSM without the WCT. By means of two complementary theoretical approaches, i.e. the continuum-model method and the lattice-model method, the electronic transmission probability, the conductivity and the Fano factor as functions of the incident electron energy are calculated respectively. We find that the WCT can give rise to nontrivial intervalley scattering, as a result, the Klein tunneling is notably suppressed. More importantly, the minimal conductivity of a WSM shifts in energy from the Weyl nodal point. The Fano factor of the shot noise deviates obviously from the sub-Poissonian value in a two dimensional WSM with the WCT.